2020
DOI: 10.1177/0145561320940135
|View full text |Cite
|
Sign up to set email alerts
|

5 Years of Diode Laser “Π” Technique for Bilateral Vocal Fold Immobility: A Technique That Improves Airway and Is Friendly to the Voice

Abstract: Background: To demonstrate the efficacy of a new laser surgical technique for bilateral vocal fold immobility (BVFI) on postoperative quality of voice and swallowing. Methods: Prospective study in a tertiary university hospital and a private hospital. Patients with iatrogenic BVFI were included. Outcome measures were Voice Handicap Index 10, 10-item Eating Assessment Tool, flexible laryngoscopy, and success of decannulation. Results: Forty patients with post thyroidectomy BVFI were initially enrolled in our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…In case of insufficient benefit from unilateral posterior cordotomy, bilateral posterior cordotomy could be considered. Many authors proposed bilateral posterior cordotomy as the first procedure for patients with BVFP 35‐38,73‐75 . The mean decannulation rate of bilateral posterior transverse cordotomy was 76.6% (range: 0%‐100%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In case of insufficient benefit from unilateral posterior cordotomy, bilateral posterior cordotomy could be considered. Many authors proposed bilateral posterior cordotomy as the first procedure for patients with BVFP 35‐38,73‐75 . The mean decannulation rate of bilateral posterior transverse cordotomy was 76.6% (range: 0%‐100%).…”
Section: Resultsmentioning
confidence: 99%
“…A study reported improvements of VHI 516 days after the procedure 38 . The swallowing improved 73 or did not change from pre‐ to postsurgery 37 . The revision rate of bilateral posterior cordotomy ranged from 0% to 46.7% and was mostly related to the management of granuloma, 38 or fibrosis/scaring of the sectioned vocal cord 74 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, patients with contact granuloma, subglottic stenosis and tracheal lesions showed partial remission with laser surgery. Recently, Karkos et al [ 30 , 31 ] demonstrated the efficacy of a new ‘‘Π’’ surgical technique (using 980 nm DL laser, 4–9 W) postoperatively to improve quality of voice and swallowing. It was proven that the 980 nm diode laser appears to be safe and ‘‘friendly’’.…”
Section: Introductionmentioning
confidence: 99%